2012
DOI: 10.1007/s10493-012-9520-6
|View full text |Cite
|
Sign up to set email alerts
|

The silk road of Tetranychus urticae: is it a single or a double lane?

Abstract: Tetranychus urticae (Acari: Tetranychidae) is a phytophagous mite that forms huge colonies. All active members of a colony (immatures and matures, females and males) spin silken threads. These mites construct a common web that protects the colony from external aggression. The silk coverage is well-known to provide advantages to the colony but very little is known about the characteristics of the threads themselves. Here is the first quantification of the diameter of silken threads spun by two different stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…The basic dimension features, such as length, width and area (Table 1) were significantly different for all distinct mite groups. The observed ranges for the length of adult mites (Table 3) were within the ranges given by Newcomer and Yothers (1929) and Considine (1995) in the case of the female European red mite, and by Clotuche et al, (2012) and Meena et al, (2013) in the case of the two-spotted spider mite. The adult female European red mites were characterized by a larger area and width, while the adult two-spotted spider mites displayed the longest mean length.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The basic dimension features, such as length, width and area (Table 1) were significantly different for all distinct mite groups. The observed ranges for the length of adult mites (Table 3) were within the ranges given by Newcomer and Yothers (1929) and Considine (1995) in the case of the female European red mite, and by Clotuche et al, (2012) and Meena et al, (2013) in the case of the two-spotted spider mite. The adult female European red mites were characterized by a larger area and width, while the adult two-spotted spider mites displayed the longest mean length.…”
Section: Resultssupporting
confidence: 85%
“…Similarly, Meena et al, (2013) found that adult females measured 0.421-0.686 mm (with a mean of 0.472 ± 0.016 mm) in length and 0.226-0.417 mm (with a mean of 0.271 ± 0.08 mm) in width. However, according to Clotuche et al, (2012) the mean body length of adult females is only 0.348 ± 0.047 mm. In the case of European red mite (Panonychus ulmi Koch), the length of the adult female body varies between 0.32 and 0.37 mm (Newcomer and Yothers, 1929), but some researchers report, however, that it is about 0.4 mm (Considine, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…They generate silk balls that may give refuge to hundreds of mites and are used as aerial dispersal elements spread either by wind or animal transport [15]. Besides, silk webbing over leaf surfaces protects the mite colony from external aggressions, is used for mite locomotion and acts as a pheromone substrate [16,17] (Figure 1d).…”
Section: Introductionmentioning
confidence: 99%
“…This, together with the use of agricultural plants as a food source (more than 900 plant species including field crops, horticultural crops, greenhouse vegetables and ornamental plants; Bolland et al, 1998;Migeon andDorkeld, 2006-2010), has made this species a major pest. One of the characteristics of T. urticae is its abundant silk production due to a continuous silk deposit while walking (Clotuche et al, 2012a;Saito, 1977). A dense collection of silken threads -called webbing or web -is deposited on infested foliage, and plays many positive roles (Clotuche, 2011;Helle and Sabelis, 1985;Sabelis and Bakker, 1992;Saito, 2009) such as the protection of individuals against biotic (Hoy and Smilanick, 1981) and abiotic agents (Hazan et al, 1975).…”
Section: Introductionmentioning
confidence: 99%